Performance improvements in Stirling cycle machines by a modified appendix gap geometry. (20th September 2021) - Sauer, Jan; Kühl, Hans‐Detlev
Summary: In this contribution, the optimization potential of the seal geometry in Stirling machines is explored both numerically and analytically, leading to a significant reduction of the related losses which are often referred to as appendix gap losses. These are induced by the narrow gap between the displacer and the cylinder and have mostly been underestimated so far. A recent experimental investigation revealed large optimization potentials by reduction of the seal and cylinder wall diameter near the seal, resulting in reduced appendix gap losses and further indirect positive effects. In this work, these experimental findings could be reproduced by a one‐dimensional differential simulation model at a fully satisfyingaccuracy. Furthermore, these investigations reveal that the optimum geometry is largely machine‐dependent. To provide an easily applicable design rule for this optimum geometry, a refined analytical model for the mass flow at the top of the gap is derived, which is based on a phasor analysis and a linearized mass balance that also accounts for changes in the spatial mean gas temperature in the gap. The optimum design predicted by this model is very close to numerical optimization results and sufficiently accurate under practical aspects. Furthermore, this model contributes to a better theoretical understanding of the loss mechanisms in the gap. Abstract : Experimentally observed performance improvements of Stirling engines by a modified displacer seal geometry are reproduced by numerical modelling. Furthermore, they are theoretically confirmed by an enhanced analytical model based on a phasor analysis describing the cyclic state changes of the gas in the appendix gap above the seal. An easily applicable set of closed‐form design equations for an optimum seal geometry is derived, which matches the results of numerical optimizations with practically satisfying accuracy.